Light Metals 2018 (Cham : Springer International Publishing, 2018)
The Light Metals symposia at the TMS Annual Meeting & Exhibition present the most recent developments, discoveries, and practices in primary aluminum science and technology. The annual Light Metals volume has become the definitive reference in the field of aluminum production and related light metal technologies. The 2018 collection includes papers from the following symposia: 1.Alumina and Bauxite 2.Aluminum Alloys, Processing, and Characterization 3.Aluminum Reduction Technology 4.Cast Shop Technology 5. Cast Shop Technology: Energy Joint Session 6. Cast Shop Technology: Fundamentals of Aluminum Alloy Solidification Joint Session 7. Cast Shop Technology: Recycling and Sustainability Joint Session 8. Electrode Technology for Aluminum Production 9. Perfluorocarbon Generation and Emissions from Industrial Processes 10. Scandium Extraction and Use in Aluminum Alloys .
Aluminum Reduction Technology -- Maximizing Previous Pot Design to Have Higher Capacity -- On the Use of Multivariate Statistical Methods to Detect, Diagnose and Mitigate Abnormal Events in Aluminium Smelters -- Spike Detection Using Advanced Analytics and Data Analysis -- Speed, Agility and Simplicity (SAS) Recovery of Reduction Line-5 in Alba -- Partial Repair and Restart of a Damaged Aluminium Reduction Cell -- Discussion on Alumina Dissolution and Diffusion in Commercial Aluminum Reduction Cell -- Investigation of Alumina Concentration Gradients within Hall-Héroult Electrolytic Bath -- Study of Alumina Dissolution in Cryolitic Bath to the Vertical Soderberg (VSS) Aluminum Production Process -- Impacts of Sodium on Alumina Quality and Consequences for Current Efficiency -- Alucell: A Unique Suite of Models to Optimize Pot Performances and Design -- Anode Bottom Burnout Shape and Velocity Field Investigation in a High Amperage Electrolysis Cell -- CFD Modelling of Alumina Feeding -- Effect of Steel Multi-collector Bars on Current Density and Magnetohydrodynamic Stability in an Aluminum Reduction Cell -- Numerical Simulation Study on Gas Collecting System of 400kA Grade Aluminum Electrolytic Cell -- Study on 3D Full Cell Ledge Shape Calculation and Optimal Design Criteria by Coupled Thermo-flow Model -- The Successful Implementation of Energy Saving Technology Based on Steady Flow and Heat Preservation -- Current Efficiency in Hall-Héroult Cells: The Role of Mass Transfer at the Cathode -- Effects of Current Density on Current Efficiency in Low Temperature Electrolysis with Vertical Electrode Structure -- Relationship between Aluminium Electrolysis Current Efficiency and Operating Condition in Electrolyte Containing High Concentration of Li and K -- Evaluating Effects of Future Shared Mobility and Electrification Trends on Key Intermediate Indicator of Aluminum Transportation Demand: US Vehicle Fleet Size -- Improvement in Smelter Process Analysis through EGA Lab Modernization -- Two-stage Pot Gas Treatment Technology Allowing the Production of Sodium Sulfate -- Improved Abart Gas Treatment and Alumina Handling at the Karmøy Technology Pilot (KTP) -- Alternative Roof-vent Emission Monitoring Method -- SPL: An Update -- Bubble Dispersion States in the Zinc Oxide Desulfurization Injection Blow Tank -- Decision Matrix for Pneumatic Conveying and Distribution of Material -- Very Low Energy Consumption Cell Designs: The Cell Heat Balance Challenge -- APXe Cell Technology: 7 Years of Low Energy Operation -- Development and Industrial Application of NEUI600 High Efficiency Aluminum Reduction Cell -- RA-550 Cell Technology: UC RUSAL's New Stage of Technology Development -- DX+ Ultra Industrial Version: Preheat Start up and Early Operation -- Selecting Technology for Achieving 300,000 T/Year - Why Do We Need to Compete Pot Technology? -- AP44 Development at Alma -- EGA New D20+ Technology with Reduced Energy Consumption -- Potline Start up without Anode Effect Frequency -- Thermo-electrical Modeling of an Aluminum Reduction Cell -- Restarting Electrochemical Cell with a Cold Metal (D18 Cell) -- Part 4. Cast Shop Technology -- Root Cause Analysis Findings of a Force 3 Explosion -- Condensation Warning System for Dry Material Storage -- A New Aluminium Crucible Skimmer (ACS) for Smelter Plants - Main Benefits Further to Two Years of Experimentation in Industrial Environment -- Drive-in Feeding of Crucibles for Casting Machine -- In-line Salt Fluxing Process with an FFDTM Industrial Experience with a Box-Type Degasser -- The "Alcoa Filter System": A Cost Effective Solution for Enhanced CFF Performance -- Continuous Centrifugal Casting: A Revolutionary Process for Casting Aluminium Tubes -- Development of a Prototype Unit for Continuous Centrifugal Casting of Aluminium Tubes -- Constellium's R&D on the Use of Power Ultrasound in Liquid Aluminum: An Overview -- Molten Metal Cleanliness: Recent Developments to Improve Measurement Reliability -- On-site Benchmark of LiMCA II vs. LiMCA III for Monitor.
Chemistry and Materials Science
text file PDF
Keywords: Metals; Materials science; Engineering-Materials.